Biology of Triatoma carcavalloi Jurberg, Rocha & Lent, 1998 under laboratory conditions - Cardozo-de-almeida, Margareth; Neves, Simone Caldas Teves; Almeida, Carlos Eduardo De; Lima, Nathanielly Rocha Casado De; Oliveira, Maria Luiza Ribeiro De; Santos-mallet, Jacenir Reis Dos; Gonçalves, Teresa Cristina Monte (Sociedade Brasileira de Medicina Tropical - SBMT, 2014)
Introduction Triatoma carcavalloi is a wild species that is found in sympatry with Triatoma rubrovaria and Triatoma circummaculata, which are vectors of Trypanosoma cruzi currently found in rural areas of Rio Grande do Sul, Brazil. Methods Fertility was assessed and to determine the incubation period, the eggs were observed until hatching. The first meal was offered to 1st stage nymphs. The intermolt period was also determined. The number of blood meals was quantified at each nymphal stage and the resistance to fasting as the period between ecdysis and death. Mortality was assessed and longevity was determined by recording the time that elapsed from molting to the adult stage and until death. The developmental cycle was assessed by recording the length in days of each stage from molting to adult hood. Results The average incubation period was 22.7 days. The average first meal occurred 3.1 days after hatching. The 5th stage nymph to adult intermolting period was the longest at 193.4 days. The average number of feedings during nymphal development was 13.4. The resistance to fasting assay indicated that the 3rd, 4th and 5th stage nymphs presented higher resistance than did adults. The highest mortality rate was observed in the 3rd stage nymphs (22.2%). The average length of adult survival was 25.6 weeks, and the average total life cycle lasted 503.4 days. Conclusions This study is the first report on the biology of T. carcavalloi that fed on mice. The presented findings expand the bionomic knowledge of these species.
Keywords: Triatominae; Triatoma carcavalloi; Biological behavior